Board gender diversity and corporate social responsbility - Sanyaolu Wasiu Abiodun; Sanni Micheal Rotimi; Sultanova Menslu; Kenzhin Zhaxat; Kuangaliyeva Tursynzada; Adesina Biola Hammed (Cogent Business & Management, 2023)
While board gender diversity (BGD) and corporate social responsibility (CSR) have become topics of global interest among practitioners, regulators and academician, most existing studies, particularly on Nigerian banks, have majorly concentrated on the effect of BGD on financial performance. It has also been observed that the few studies on banks have mostly viewed the nexus from static perspective. To the best of our knowledge, there is no study that has used dynamic data analysis approach involving generalised method of moment (GMM) on BGD and CSR nexus of Nigerian banks. To this extent, this study aims to examine the effect of BGD on CSR of 12 listed deposit money banks in Nigeria from 2012 to 2021 using dynamic analysis involving GMM. The study is anchored on three theories, which are stakeholders' theory, legitimacy theory and gender socialization theory. Findings show that BGD has no significant positive effect on CSR, implying that BGD does not affect firm commitment to CSR endeavours. The study recommends that more women should be appointed to the boardroom and given equal opportunities as their male counterparts in corporate and strategic decision-making so as to foster good relationship with stakeholders. The outcome of our study is of significant relevance to bank stakeholders such as managers, regulators, policymakers and academician on the need for more women representation and participation in corporate and strategic decision-making.
Keywords: 650; board gender diversity; corporate social responsibility and generalized method of moment